2019
DOI: 10.3892/mmr.2019.10409
|View full text |Cite
|
Sign up to set email alerts
|

RSRC1 suppresses gastric cancer cell proliferation and migration by regulating PTEN expression

Abstract: Arginine/serine-rich coiled coil 1 (RSRC1) is a gene which plays a significant role in the constitutive and alternative splicing of mRNA and transcriptional regulation. It has been implicated in various neurological disorders, as well as in cancer. However, its role in gastric cancer (GC) remains unknown. Thus, the present study aimed to investigate the role of RSRC1 in GC. RSRC1 expression in GC tissues was determined by RT-qPCR and immunohistochemical staining. The effects of RSRC1 on cell proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…PUSL1 encodes an inner membrane–associated mitochondrial matrix protein required for efficient mitochondrial translation ( 28 ). RSRC1 encodes a member of the serine- and arginine-rich–related protein family, associated with altered brain function in schizophrenia, and may also be associated with cancer cell proliferation and migration ( 29 , 30 ). Genome-wide association studies have shown that single-nucleotide polymorphisms of RSRC1 are associated with schizophrenia ( 31 , 32 ), and its mutation causes intellectual disability, aberrant behavior, hypotonia, and mild facial dysmorphism ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…PUSL1 encodes an inner membrane–associated mitochondrial matrix protein required for efficient mitochondrial translation ( 28 ). RSRC1 encodes a member of the serine- and arginine-rich–related protein family, associated with altered brain function in schizophrenia, and may also be associated with cancer cell proliferation and migration ( 29 , 30 ). Genome-wide association studies have shown that single-nucleotide polymorphisms of RSRC1 are associated with schizophrenia ( 31 , 32 ), and its mutation causes intellectual disability, aberrant behavior, hypotonia, and mild facial dysmorphism ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Total proteins were extracted from cultured GC cells with RIPA buffer, and the supernatants were diluted in 5×SDS loading buffer after calculating protein concentration with a Pierce BCA protein assay kit (Takara, Japan). Western blot assay was carried out in accordance with the previous report (Yu et al 2019 ). The signal bands were detected by Odyssey Infrared Imaging System (Li-COR Biosciences) based on manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding protein localises to lipid droplets and increased levels of lipid droplets have been found in EA versus BE and BE versus normal tissue 50 . RSRC1 at 3p25 is involved in mRNA splicing and may suppress gastric cancer cell proliferation 51 . BTN3A2 at 4q34 is a coregulator of T-cells and NK-cells in immune responses 52.…”
Section: Discussionmentioning
confidence: 99%